Understanding the public health consequences of suspending a rural syringe services program: a qualitative study of the experiences of people who inject drugs - Sean T. Allen; Suzanne M. Grieb; Allison O'Rourke; Ryan Yoder; Elise Planchet; Rebecca Hamilton White; Susan G. Sherman (BMC, 2019)
Abstract Background Syringe services programs (SSPs) are evidence-based interventions that are associated with decreases in prevalence and incidence rates of HIV and viral hepatitis among people who inject drugs (PWID). SSPs are also effective conduits to deliver overdose prevention resources among PWID. In December 2015, the Kanawha-Charleston Health Department (KCHD) in West Virginia implemented a SSP; however, the program was indefinitely suspended in early 2018 following policy changes that would have forced the program to operate in ways that conflicted with established best practices. The purpose of this research is to explore the public health implications of the suspension of the KCHD SSP among rural PWID. Methods We conducted semi-structured interviews with 27 PWID (59.3% male, 88.9% White) to explore access to sterile injection equipment and overdose prevention resources, high-risk injection practices, and HIV risk perceptions following the KCHD SSP suspension. Participants were recruited from street locations frequented by PWID. Interviews were audio-recorded and transcribed verbatim. We employed an iterative, modified constant comparison approach to systematically code and synthesize textual interview data. Results Participants described the KCHD SSP as providing a variety of harm reduction services to PWID and being able to speak honestly with SSP staff about their drug use without fear of stigmatization. The suspension of the KCHD SSP fundamentally changed the public health landscape for PWID, ushering in a new era of increased risks for acquiring bloodborne infections and overdose. PWID described more frequently injecting with used syringes and engaging in a range of high-risk injection practices after the SSP was suspended. PWID also discussed having decreased access to naloxone and being less likely to get routinely tested for HIV following the KCHD SSP suspension. Conclusions This research demonstrates that the suspension of a SSP in rural West Virginia increased risks for HIV/HCV acquisition and overdose among PWID. The suspension of the SSP led to community-wide decreases in access to sterile injection equipment and naloxone among PWID. The suspension of the KCHD SSP should be viewed as a call to action for sustaining evidence-based interventions in the face of sociopolitical forces that attempt to subvert public health.